A novel method for imitating nacre by utilizing magnetic graphene oxide and its magnetic field alignment in polymer nanocomposites. (15th February 2018) - Liu, Zhenxiang; Jiao, Weicheng; Yan, Meiling; Li, Jun; Ding, Guomin; Wang, Rongguo
Abstract: The way gas molecules penetrate the resin matrix composites are generally divided into diffusion penetration and destruction penetration. Through theoretical analysis, the larger the nanoscale layers, the smaller the penetration effect in the directional nanosheets reinforced resin matrix composites. To control destruction penetration, the cracks should be reduced by toughening resin matrix composites. In order to solve these two kinds of leakage, the magnetic graphene oxide is connected to mimic nacre while L- glutamic acid is used as binder and the directional solidification is also utilized. Compared with pure resin, only 0.13 wt% monolithic magnetic graphene oxide and its interbed reinforced composites can reduce the leakage of He by 36.4% and 52.0% respectively, and the toughness of composites is validated to increase 4.0% and 20.3% respectively. This toughening mechanism is similar to that of nacre.